Detection of biofilm formation by Escherichia coli with its antibiogram profile - Risal, Gaurab; Shrestha, Aayush; Kunwar, Saroj; Paudel, Gajal; Dhital, Rameshwor; Budha, Man Bahadur; Nepal, Rupa (International Journal Of Community Medicine And Public Health, 2018)
Background: In urinary tract infections, an important role is played by bacterial biofilms which are responsible for persistence infections together with the antimicrobial resistance. Higher resistance can be seen in biofilm forming uropathogens in comparison with free-floating bacteria. So, the present study was performed with a goal to find the prevalence of biofilm formation and also the antimicrobial resistant pattern of uropathogens. Methods: A descriptive method was conducted at Modern Technical College, Sanepa, Lalitpur in samples isolated from UTI suspected patients. The overall duration of this study was approximately 3 months. Total of 50 isolated E. coli was tested for biofilm formation and antimicrobial susceptibility testing was done by Kirby-Bauer disc diffusion method on Mueller Hinton agar as per CLSI guidelines. Results: From the 50 isolates of E. coli, 32 were biofilm producers (3 strong and 29 moderate) and 18 were weak/non-biofilm producers. Among the biofilm producers, cefotaxime was more resistant in 20 of the isolates followed by ceftriaxone in 16 and amoxyclav in 13, whereas amikacin was least resistant in 2 of the isolates. Conclusions: Among the isolated E. coli, biofilm-forming isolates showed higher antimicrobial resistance as compared to the non-biofilm producer. Thus, uropathogen should be routinely screened for biofilm formation.